2013
DOI: 10.1016/j.epsl.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Subduction zone fluxes of halogens and noble gases in seafloor and forearc serpentinites

Abstract: Kendrick-11Dec'12.docx Click here to view linked References serpentinites trap noble gases and halogens that originate from seawater, diverse crustal lithologies and organic matter. Combined with previous analyses of metamorphosed serpentinites, the new data suggest that approximately 60-70% of the 36 Ar entering subduction zones in serpentinites is lost from chrysotile and/or antigorite and could potentially escape through the forearc. An additional, ~20-30 % of the 36 Ar entering subduction zones in serpenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
115
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 77 publications
13
115
1
1
Order By: Relevance
“…It has been proposed that element extraction from such rocks is boosted by fluids released by serpentinite dehydration Kessel et al, 2005b;Spandler and Pirard, 2013). However, it is increasingly shown that serpentinites have the capacity to store volatiles and fluid-mobile elements sequestered during oceanic alteration, or during interaction with slab-fluids circulating in subduction-zone environments (Hattori and Guillot, 2003;Scambelluri et al, 2004a;Sharp and Barnes, 2004;Savov et al, 2005;Deschamps et al, 2011Deschamps et al, , 2013Kendrick et al, 2011Kendrick et al, , 2013John et al, 2011;Spandler et al, 2011;Alt et al, 2013;Evans et al, 2014;Bebout, 2014). Once stored in serpentinite, these elements are progressively released by the prograde dehydration reactions chrysotile ± lizardite + SiO 2,aq = antigorite + fluid,…”
Section: Introductionmentioning
confidence: 98%
“…It has been proposed that element extraction from such rocks is boosted by fluids released by serpentinite dehydration Kessel et al, 2005b;Spandler and Pirard, 2013). However, it is increasingly shown that serpentinites have the capacity to store volatiles and fluid-mobile elements sequestered during oceanic alteration, or during interaction with slab-fluids circulating in subduction-zone environments (Hattori and Guillot, 2003;Scambelluri et al, 2004a;Sharp and Barnes, 2004;Savov et al, 2005;Deschamps et al, 2011Deschamps et al, , 2013Kendrick et al, 2011Kendrick et al, , 2013John et al, 2011;Spandler et al, 2011;Alt et al, 2013;Evans et al, 2014;Bebout, 2014). Once stored in serpentinite, these elements are progressively released by the prograde dehydration reactions chrysotile ± lizardite + SiO 2,aq = antigorite + fluid,…”
Section: Introductionmentioning
confidence: 98%
“…Kendrick et al, 2014Kendrick et al, , 2013. However, the heterogeneity of subducted rocks requires the use of geochemical proxies for source identification prior to determination of regional mass budgets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Subduction of crustal material is responsible for providing the return flow of volatile species to the mantle from the Earth's surface environment (Hilton et al 2002;Dasgupta and Hirschmann 2010;Kendrick et al 2013). Experiments have demonstrated that hydrous materials undergo deserpentinisation and melting at sub-arc depths (2-6 GPa) causing the loss of the majority of the water stored in subducted material (e.g.…”
Section: Depth Of Individual Inclusion Formationmentioning
confidence: 99%